Hyperglucose Contributes to Periodontitis: Involvement of the NLRP3 Pathway by Engaging the Innate Immunity of Oral Gingival Epithelium. Issue 2 (1st February 2015) - Huang, Xin; Yang, Xi; Ni, Jia; Xie, Baoyi; Liu, Yeungyeung; Xuan, Dongying; Zhang, Jincai
Abstract : Background: The NLRP3 inflammasome is essentially a family of intracellular innate immune sensors that can respond to bacterial challenge and initiate early host immunity responses. However, the involvement and possible molecular mechanism of the NLRP3 pathway in the context of chronic periodontitis (CP) and diabetes mellitus have yet to be fully elucidated. Methods: Gingival tissues were collected from patients with CP and/or type 2 diabetes mellitus (T2DM), and the expression of NLRP3 and interleukin (IL)‐1β was analyzed by immunohistochemistry. To explore the possible molecular mechanism, human gingival epithelial cells (HGECs) were established in vitro and challenged with lipopolysaccharide (LPS) and/or high glucose. High extracellular K + was applied as an inhibitor of NLRP3. The NLRP3 pathway was analyzed by immunocytochemistry and quantitative polymerase chain reaction. Results: Compared with control individuals, NLRP3 and IL‐1β were significantly upregulated in oral gingival epithelium of patients with CP and/or T2DM ( P <0.05). The expression of NLRP3 was significantly upregulated in HGECs when stimulated in vitro by LPS or high glucose ( P = 0.00). The simultaneous stimulation of LPS and high glucose contributed to significant upregulation of NLRP3 expression versus LPS or high glucose alone ( P = 0.00). Although expression of caspase 1 and IL‐1β protein were increased in HGECs when stimulated by LPS, they were partially inhibited after the NLRP3 was successfully blocked. Conclusion: For patients with T2DM and CP, hyperglycemic status may exacerbate the inflammation state of gingival tissue by activating the NLRP3 pathway, and this abnormal host inflammatory response may contribute to further tissue breakdown.